Uric acid regulates α-synuclein transmission in Parkinsonian models - Shin, Yu Jin; Kim, Yeon Ju; Lee, Ji Eun; Kim, Yi Seul; Lee, Jung Wook; Kim, HyeonJeong; Shin, Jin Young; Lee, Phil Hyu (Frontiers in Aging Neuroscience, 2023)
Ample evidence demonstrates that α-synuclein (α-syn) has a critical role in the pathogenesis of Parkinson’s disease (PD) with evidence indicating that its propagation from one area of the brain to others may be the primary mechanism for disease progression. Uric acid (UA), a natural antioxidant, has been proposed as a potential disease modifying candidate in PD. In the present study, we investigated whether UA treatment modulates cell-to-cell transmission of extracellular α-syn and protects dopaminergic neurons in the α-syn-enriched model. In a cellular model, UA treatment decreased internalized cytosolic α-syn levels and neuron-to-neuron transmission of α-syn in donor-acceptor cell models by modulating dynamin-mediated and clathrin-mediated endocytosis. Moreover, UA elevation in α-syn-inoculated mice inhibited propagation of extracellular α-syn which decreased expression of phosphorylated α-syn in the dopaminergic neurons of the substantia nigra leading to their increased survival. UA treatment did not lead to change in markers related with autophagolysosomal and microglial activity under the same experimental conditions. These findings suggest UA may control the pathological conditions of PD via additive mechanisms which modulate the propagation of α-syn.